2019
DOI: 10.1097/md.0000000000016509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of amyloid-PET in daily clinical management of patients with cognitive impairment fulfilling appropriate use criteria

Abstract: To evaluate the use of amyloid-positron emission tomography (PET) in routine clinical practice, in a selected population with cognitive impairment that meets appropriate use criteria (AUC). A multicenter, observational, prospective case-series study of 211patients from 2 level-3 hospitals who fulfilled clinical AUC for amyloid-PET scan in a naturalistic setting. Certainty degree was evaluated using a 5-point Likert scale: 0 (very low probability); 1 (low probability); 2 (intermediate probability); 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
4
1
Order By: Relevance
“…In a previous report, amyloid PET was associated with changes in core elements of management in more than 60% and changes in diagnosis in more than 35% of patients in the IDEAS study . These changes may translate into improved health outcomes by refining the diagnosis and treatment plan and may, in and of themselves, justify the clinical utility of amyloid PET, despite the null association with hospitalizations and ED visits found in the present study. Use of symptomatic drugs for AD, such as cholinesterase inhibitors and memantine, which in the IDEAS study were altered in 43% of patients after amyloid PET, had a modest association with rates of hospitalizations and time to institutionalization in a skilled nursing facility, and other studies suggested an association with reduced risk of mortality .…”
Section: Discussioncontrasting
confidence: 68%
“…In a previous report, amyloid PET was associated with changes in core elements of management in more than 60% and changes in diagnosis in more than 35% of patients in the IDEAS study . These changes may translate into improved health outcomes by refining the diagnosis and treatment plan and may, in and of themselves, justify the clinical utility of amyloid PET, despite the null association with hospitalizations and ED visits found in the present study. Use of symptomatic drugs for AD, such as cholinesterase inhibitors and memantine, which in the IDEAS study were altered in 43% of patients after amyloid PET, had a modest association with rates of hospitalizations and time to institutionalization in a skilled nursing facility, and other studies suggested an association with reduced risk of mortality .…”
Section: Discussioncontrasting
confidence: 68%
“…Based on the issue examined in the papers, we have identified three main outcome domains: (a) clinician-centered outcomes , quantifying the impact on the diagnostic procedure in terms of physician’s diagnostic confidence and patient management; (b) patient- and caregiver-centered outcomes , operationalizing the ultimate target of patients benefit; and (c) health economics-centered outcomes , consisting either of costs alone or of combined evidence of costs and other impacts on health resource utilization (Table 2 ). (a) Most of the selected studies (25/32, 78%) [ 9 , 11 , 13 35 ] included outcomes belonging to the clinician-centered domain and assessed the incremental diagnostic value for physicians, e.g., in terms of diagnostic change and increased diagnostic confidence (25/32, 78%), and changes in the planning of patient management (17/32, 53%) (Table 2 ). Amyloid-PET led to diagnostic revision in 19–79% of cases, to increased diagnostic confidence (9–49%), and to revise management plans (24–89% of cases) [ 13 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…(a) Most of the selected studies (25/32, 78%) [ 9 , 11 , 13 35 ] included outcomes belonging to the clinician-centered domain and assessed the incremental diagnostic value for physicians, e.g., in terms of diagnostic change and increased diagnostic confidence (25/32, 78%), and changes in the planning of patient management (17/32, 53%) (Table 2 ). Amyloid-PET led to diagnostic revision in 19–79% of cases, to increased diagnostic confidence (9–49%), and to revise management plans (24–89% of cases) [ 13 35 ]. (b) Patient- and caregiver-centered outcomes are reported in 28% (9/32) [ 9 , 11 , 24 , 30 , 33 , 36 39 ] of the studies and mainly assessed the patients’ and caregivers’ distress after amyloid-pet-based diagnosis disclosure (8/32, 25%) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several additional longitudinal studies published since the systematic review have each identified changes in diagnosis, diagnostic confidence, and/or patient manage-ment. [16][17][18][19][20] One study was from the United Kingdom. This retrospective single-arm study examined the utility of aPET with 18F-florbetapir for patients attending a tertiary referral clinic.…”
Section: þþmentioning
confidence: 99%